Analysis Of The Effectiveness Of Total Neoadjuvant Therapy In The Treatment Of Patients With Pancreatic Cancer - Akhmadzhanov Elmurodjon Burkhanidinovich (Genius Journals, 2025)
Pancreatic cancer remains one of the most aggressive and lethal malignancies in modern oncology and continues to pose a major clinical challenge worldwide. Pancreatic ductal adenocarcinoma (PDAC) accounts for more than 90% of all pancreatic malignancies and is characterized by rapid disease progression, early metastatic spread, and resistance to many conventional treatment modalities. Despite representing a smaller proportion of overall cancer incidence, pancreatic cancer ranks among the leading causes of cancer-related mortality, with five-year survival rates remaining below 15% in most populations. This unfavorable prognosis reflects a combination of late diagnosis, complex tumor biology, and limited therapeutic effectiveness
Keywords: diagnosis; mortality; biology; therapeutic